Bullying at School and Labour Market Outcomes - Nick Drydakis (Institute for the Study of Labor (IZA), 2013)
This study examines the long-term correlates of bullying in school with aspects of functioning in adult employment outcomes. Bullying is considered and evaluated as a proxy for unmeasured productivity, and a framework is provided that outlines why bullying might affect employment outcomes through differences in skills and traits. Using Bivariate and Heckit models we employ a variety of specifications and find several interesting patterns. The regression outcomes suggest that labour force participation, employment rate and hourly wages are negatively affected by bullying. In addition, men, homosexuals, immigrants, unmarried people, those having higher negative mental health symptoms, and those having lower human capital are more negatively affected by bullying in terms of labour force participation, employment probability, and hourly wages. Moreover, Oaxaca-Blinder decompositions suggest that labour force participation gaps, employment gaps and hourly wage gaps between minority and majority groups, especially for gay men and the disabled, can be explained by bullying incidents. It seems likely that having been a victim of bullying also has economic implications later in life due to withdrawal from the labour market and lower wages.
Keywords: E24; J21; J24; 330; bullying; personality traits and processes; human capital; labour force; employment; wages